Filmmaker-in-Residence: The Complete Collection - Cizek, Katerina; Frise, Heather; Guddat, Monica
The National Film Board of Canada placed media maker Katerina Cizek "in residence" at Toronto’s inner-city St. Michael’s Hospital, renowned for innovation in patient care and research. The result is a collection of multi-platform documentaries that prove digital storytelling can work as a tool for social action. Young, homeless mothers problem-solve through "video bridging". Community-based care saves lives in southern Africa. Suicide intervention therapy and film animation intertwine. Throughout, doctors, nurses and media makers work together to create transformative tools. "The 7 Interventions of Filmmaker-in-Residence" charts the project’s five-year history, investigating the creative process from within as media makers join doctors, nurses, researchers and patients at the front-lines of urban and global health. "Filmmaker-in-Residence" is now recognized around the world as a model for social, cinematic and creative innovation. [www.onf-nfb.gc.ca]
Keywords: DVD-Video